Exploring Influential Factors on Online Groceries Shopping Purchase Intentions Among Customers in Jabodetabek Area - Rahmawati, Keny; Putri, Dianty Anggraini (Jurnal Paradigma, 2022)
This study applied a qualitative approach to investigate the underlying influences on consumers’ online grocery shopping from the intention generation phase to intention execution phase in the perspectives of purchase intention and the intention–behaviour gap (IBG). Research data were derived from semi-structured in-depth interviews with 10 consumers and analyzed using grounded theory. The findings identified factors that influenced intentions and the IBG in the process of consumers’ online grocery shopping. Specifically, these findings reported that perceived usefulness, perceived ease of use, perceived risk of COVID-19, social influence, and enjoyable shopping experiences were identified as major drivers for generating consumers’ online purchase intentions. Difficulty in transaction, late delivery, incomplete information, bad packaging, and difficulty with site navigation were factors triggering the gap between online grocery purchase intentions and behaviours These findings will help stakeholders build future policy and suitable strategies to better promote online grocery shopping in the Jabodetabek context.